Adaptive phenotype of microglial cells during the normal postnatal development of the somatosensory "Barrel" cortex. Issue 10 (26th July 2013) - Arnoux, Isabelle; Hoshiko, Maki; Mandavy, Léo; Avignone, Elena; Yamamoto, Nobuhiko; Audinat, Etienne
<x xml:space="preserve">Abstract</x> Accumulative evidence indicates that microglial cells influence the normal development of central nervous system (CNS) synapses. Yet, the functional properties of microglia in relation with synapse development remain unclear. We recently showed that in layer 4 of the whisker‐related barrel field of the mouse somatosensory cortex, microglial cells are recruited only after postnatal day (P)5 in the center of the barrels where thalamo‐cortical synapses are concentrated and begin their maturation. In the present study, we analyzed the phenotype of microglia during this developmental process. We show that between P5 and P7 microglial cells acquire a more ramified morphology with a smaller soma, they express classical markers of microglia (Iba1, CD11b, and CD68) but never markers of activation (Mac‐2 and MHCII) and rarely the proliferation marker Ki67. Electrophysiological recordings in acute cortical slices showed that at P5 a proportion of layer 4 microglia transiently express voltage‐dependant potassium currents of the delayed rectifier family, mostly mediated by Kv1.3 subunits, which are usually expressed by activated microglia under pathological conditions. This proportion of cells with rectifying properties doubles between P5 and P6, in concomitance with the beginning of microglia invasion of the barrel centers. Finally, analysis of the responses mediated by purinergic receptors indicated that a higher percentage of rectifying microglia expressed functional P2Y6 and P2Y12 receptors, as compared with nonrectifying cells, whereas all cells expressed functional P2X7 receptors. Our results indicate that during normal cortical development distinct microglia properties mature differentially, some of them being exquisitely influenced by the local environment of the maturating neuronal network.GLIA 2013;61:1582–1594